2015
DOI: 10.1002/cbic.201500123
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Direct Binding of CFTR Correctors to CFTR by Using Click Chemistry

Abstract: Cystic fibrosis (CF) is a lethal genetic disease caused by the loss or dysfunction of the CF transmembrane conductance regulator (CFTR) channel. F508del is the most prevalent mutation of the CFTR gene and encodes a protein defective in folding and processing. VX-809 has been reported to facilitate the folding and trafficking of F508del-CFTR and augment its channel function. The mechanism of action of VX-809 previously has been poorly understood. In this study, we sought to answer a fundamental question underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Firstly,t he correctors must act as aphar- www.chembiochem.org macological chaperone, aiding the folding process. [34,35] Subsequently, treatment with correctors alters the interaction between CFTR and proteostasis components (CFTR interactome), thus allowing the newly synthesized CFTR to reach the plasma membrane. [20,21] Here, we have shown that administration of correctors reduces the binding of HDAC6 and 7a nd Hsp27 and 40 to CFTR.…”
Section: Ap Roteostasis Network Is Engaged In the Rescueo Fcftr By Comentioning
confidence: 99%
“…Firstly,t he correctors must act as aphar- www.chembiochem.org macological chaperone, aiding the folding process. [34,35] Subsequently, treatment with correctors alters the interaction between CFTR and proteostasis components (CFTR interactome), thus allowing the newly synthesized CFTR to reach the plasma membrane. [20,21] Here, we have shown that administration of correctors reduces the binding of HDAC6 and 7a nd Hsp27 and 40 to CFTR.…”
Section: Ap Roteostasis Network Is Engaged In the Rescueo Fcftr By Comentioning
confidence: 99%
“…Lumacaftor-corrected Phe508del-CFTR exhibited biochemical and functional characteristics similar to wild-type (WT)-CFTR (22). Mechanistic studies suggested that lumacaftor acts by directly interacting with Phe508del-CFTR and promoting its proper folding during biogenesis and processing in the ER (23, 24). In addition to Phe508del, lumacaftor also rescued the maturation of other mutations (e.g., Gly1208Asp) (24, 25).…”
Section: Lumacaftor and Ivacaftormentioning
confidence: 99%
“…Yet, we are left with many challenges in terms of disease management given, for example, the modest impact of Lumacaftor-Ivacaftor combination on mitigating F508del disease phenotype 156 or lvacaftor improving lung function in patients over 18 yrs with Arg117His variant but not in children 163 . Even if operating directly 27,58,158,164166 , such pharmacological chaperones may likely only perturb a transient state of the variant CFTR folds that contribute to the dysfunctional CFFL. Moreover, the ability of both ‘caftors’ to correct multiple CFTR variants suggests that they likely operate indirectly through the activity or influence of the PN or the SN.…”
Section: Cf Hallmark 5: Therapeutic Interventionmentioning
confidence: 99%
“…An alternative to generic heterologous cell-based HTS assays is to directly stabilize in vitro CFTR variant affected domains, such as the NBD1 domain harbouring F508del either as an isolated fragment, or as reconstituted purified protein in artificial lipid bialyers 164,169 . The goal here, for example, is to identify small molecules that chemically perturb activity, for example, based on a reporter assay that measure a change in activity (such as ATPase for NBD1 domain or chloride flux for full-length CFTR in the bilayer), or a change in structure, such as thermal denaturation/ renaturation kinetics of purified NBD1, as a surrogate metric of biological impact.…”
Section: Cf Hallmark 5: Therapeutic Interventionmentioning
confidence: 99%